Street Scenes: The Politics of Revolutionary Video in Egypt. Issue 3 (26th May 2016) - Westmoreland, Mark R.
Abstract : Images of mass protests that arose from Egypt in early 2011 enraptured global audiences with unexpected scenes of street politics and unprecedented possibilities for political change. While the presence of thousands of cellphone cameras, perhaps hundreds of thousands, provided the technology for a multitude of witnessing, the hyper-visibility of the street in times of protest made image-making practices both threatening and powerful. The recursive rehabilitation of counter-revolutionary images happened on many fronts. Western journalists have long characterized the "Arab Street" as a "barbarous urban mob" and, despite enchantment with the "Arab Spring, " still perpetuated a simplistic analysis of street politics in the region. Meanwhile local television, advertising, and music videos endlessly recycled revolutionary images in superficial modes of patriotic sentimentality; while the urban poor, unable to realize the aims of "bread, freedom, and social justice, " have suspiciously remained the unclaimed image of the Egyptian revolution. But by attending to the social life of revolutionary street media, this article reviews the potential for emerging image practice to cultivate new kinds of political subjectivity and collectivity.